Perspektif Hukum Perdata terhadap Permintaan Surat Keterangan Sakit di Indonesia: Analisis Perbandingan dengan Beberapa Negara - Esa Meirianna; Yuyut Prayuti (CV Rewang Rencang, 2025)
A medical certificate (sick note) is a document often requested by patients as an administrative requirement for their absence from work or education due to illness. However, the request for this note is often misused, whether by patients, supervisors, or medical personnel. This article discusses how the request for a sick note is viewed from Indonesian civil law’s perspective, including when the note is requested with a backdated date or under pressure/intimidation. This study also compares regulations in Germany and Japan as a basis for system improvement. Through a juridical-normative approach and literature review, it is found that such actions can be classified as unlawful acts that have implications for the civil liability of various parties. This article recommends the establishment of specific regulations to regulate the issuance of sick notes within the framework of civil legal protection and medical professional ethics.